Comparative study on gut microbiota in three Anura frogs from a mountain stream - Chen, Zhuo; Chen, Jun‐Qiong; Liu, Yao; Zhang, Jie; Chen, Xiao‐Hong; Qu, Yan‐Fu (Ecology and evolution, 2022)
Composition and diversity in gut microbiota are impacted by a wide variety of factors. The similarity of gut microbiota in related or sympatric species has been gaining recent traction. Here, 16S rRNA gene sequencing technology was employed to study the gut microbiota of three sympatric frog species, namely Odorrana tormota, O. graminea, and Amolops wuyiensis. In these three frog species, the most abundant phylum was Proteobacteria, followed by Bacteroidetes, Verrucomicrobia, and Firmicutes. The most abundant family was Burkholderiaceae in three species. The most dominant genera were Burkholderia, Caballeronia, and Paraburkholderia with the highest relative abundance in O. tormota, O. graminea, and A. wuyiensis, respectively. No differences were observed in alpha diversity indexes among the three frog species. However, bacterial similarity of gut microbiota was significantly different between O. tormota and A. wuyiensis and between O. graminea and A. wuyiensis. Metabolism‐related gene function was predominantly enriched in the gut microbiota of the three evaluated frog species. From these findings, that the relative abundance of the gut microbiota and predicted gene functions differed in three species, we conclude that there were significant differences in the gut microbiota of the three species. Similar alpha diversity and interspecific bacterial similarity in the gut might be related to bacterial transmission among the three Anura frogs evaluated in this study. These three Anura frogs are commonly observed on rocks near streams. These species are distributed along mountain streams and congregate in large numbers during the breeding reason in mountain streams. This will provide a good model for the study on the gut microbial differences in sympatric frogs.